1988
DOI: 10.1007/bf02097405
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the number of respiring bacteria in groundwater from sandy and gravelly deposits

Abstract: Samples were collected from organically polluted and unpolluted groundwater of sandy and gravelly deposits. After filtration onto polycarbonate filters (0.2μm pore size) the number of respiring bacteria was recorded by microscopically counting cells containing red INT-formazan spots, which characterize respiring bacteria. The total number of bacteria was simultaneously recorded by epifluorescence microscopy after staining with acridine orange. The number of respiring bacteria in the groundwater samples (55-490… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…The present study demonstrates that a part of the DOC (47%) is in fact biodegradable and 8 .8% of the interstitial bacteria that drifted into the River Rhone were active . This last value is similar to those observed by Marxsen (1988) in groundwater (from 0 .66 to 7 .4%) using the INT formazan staining method . The increase in DOC, BDOC, and bacterial contents in groundwater on the second day of the experiment (Fig .…”
Section: Organic Matter and Bacteria Inputssupporting
confidence: 75%
“…The present study demonstrates that a part of the DOC (47%) is in fact biodegradable and 8 .8% of the interstitial bacteria that drifted into the River Rhone were active . This last value is similar to those observed by Marxsen (1988) in groundwater (from 0 .66 to 7 .4%) using the INT formazan staining method . The increase in DOC, BDOC, and bacterial contents in groundwater on the second day of the experiment (Fig .…”
Section: Organic Matter and Bacteria Inputssupporting
confidence: 75%
“…Short rod‐shaped bacteria have some advantages over large rod‐shaped and filamentous bacteria for transport through sandy sediments (Harvey et al ., 1984). Data in this study confirm previous ones (Velasco et al ., 2008; in press) and demonstrate that mean bacterial abundance observed in this aquifer system was, at least, one order of magnitude higher than that found in other sedimentary and relatively similar aquifer ecosystems (Harvey et al ., 1984; Kölbel‐Boelke et al ., 1988; Marxsen, 1988; Hirsch & Rades‐Rohkohl, 1990; Hazen et al ., 1991; Alfreider et al ., 1997; Griebler et al ., 2002). Groundwater mean bacterial abundance found in this study was also higher than planktonic bacterial densities found in granite (Eydal & Pedersen, 2007) or rock aquifer systems (Lehman et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial ecology studies of sedimentary, relatively shallow aquifer systems are relatively abundant (Marxsen, 1988; Alfreider et al ., 1997; Martino et al ., 1998; Griebler et al ., 2002; Velasco et al ., 2008; in press), but very few exist with large spatial and temporal scales. Some of these studies have shown aquifers as more stable ecosystems, with less spatiotemporal variation in their ecological processes, than other aquatic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk water samples would contain predominantly planktonic bacteria, while sessile bacteria, which are occasionally sloughed Off, would be vastly outnumbered. Studies in other aquifers have shown that more than 90% of the microorganisms were attached to soild materials and that the morphology of attached cells was different than that of free-floating cells [15]. With the sand-trap method, however, the infrequent sloughed-off sessile cells would have an opportunity to re-attach to an uncolonized surface and form a new biofilm, hopefully similar to in situ biofilms.…”
Section: Sampling Methodsmentioning
confidence: 99%